Effectiveness of problem-based learning strategies in improving critical thinking skills of students in biology learning: A literature review - Azzahra, Fatimah Ghina; Nurhanifa, Fitria; Cahayani, Kania Putri; Akbar, Muhammad Iman; Puspitasari, Nadila Apria (Journal of Biology Creative Education, 2025)
Critical thinking skills are essential 21st-century competencies, yet Biology learning in schools often remains teacher-centered, limiting students’ active involvement in analyzing and solving problems. Problem Based Learning (PBL) offers a solution by positioning students at the center of contextual problem-solving activities. This study aims to examine the effectiveness of PBL in enhancing Biology students’ critical thinking skills through a systematic literature review (SLR) using content analysis. Data were collected from Google Scholar using the keyword “Critical Thinking Problem Based Learning in Biology Education” and screened from 28,300 articles to 10 relevant ones based on inclusion and exclusion criteria. Findings indicate an increasing research trend over the past decade. PBL effectively improves learning outcomes, critical thinking skills, and student engagement, aligning with 21st-century skills. It is concluded that PBL is an adaptive and applicable strategy to enhance the quality of Biology learning.Abstrak. Keterampilan berpikir kritis merupakan kompetensi penting abad ke-21, namun pembelajaran Biologi di sekolah masih berpusat pada guru sehingga siswa kurang terlibat aktif dalam menganalisis dan memecahkan masalah. Problem Based Learning (PBL) menjadi solusi dengan menempatkan siswa sebagai pusat pembelajaran berbasis masalah kontekstual. Penelitian ini bertujuan mengkaji efektivitas PBL dalam meningkatkan keterampilan berpikir kritis siswa Biologi melalui systematic literature review (SLR) dengan analisis konten. Data diperoleh dari Google Scholar menggunakan kata kunci “Berpikir Kritis Problem Based Learning pada Pembelajaran Biologi” dan disaring dari 28.300 artikel menjadi 10 artikel relevan sesuai kriteria inklusi dan eksklusi. Hasil kajian menunjukkan tren penelitian meningkat dalam satu dekade terakhir. PBL terbukti efektif meningkatkan hasil belajar, keterampilan berpikir kritis, dan keterlibatan siswa, serta relevan dengan keterampilan abad ke-21. Disimpulkan bahwa PBL merupakan strategi adaptif dan aplikatif untuk meningkatkan kualitas pembelajaran Biologi.